Empirical estimation of Young’s modulus for biological tissue mimics using acoustic impedance measurements: A study on agar gel tissue phantoms - Shinri Morodomi; Kazushi Ito; Satoru Maegawa; Yoshihiro Ujihara; Shukei Sugita; Masanori Nakamura (PLoS ONE, 2025)
The mechanical properties of biological tissues are significant biomarkers for diagnosing various diseases. The aim of this study was to develop an empirical formula to estimate Young’s modulus from the acoustic impedance measured by scanning acoustic microscopy. Agar, a material with mechanical properties similar to those of biological tissues, was prepared at concentrations ranging from 5% to 20%. The acoustic impedance was measured by scanning acoustic microscopy, and Young’s modulus was determined via indentation testing. The results showed that both the acoustic impedance and Young’s modulus increased with agar concentration. Theoretical models did not accurately describe the relationship between the acoustic impedance Z and Young’s modulus E; however, the empirical formula E=9.2835×10−6Z2−21.6347×106 (with E in Pa and Z in Ns/m3) provided a better fit. This formula could potentially be used to estimate Young’s modulus for biological tissues, aiding in the realistic analysis of stress fields and understanding the etiology of various diseases.